STUDY OF SOME CRITERIA EXPLOITATION OF AGRICULTURAL TECHNOLOGY IN ECONOMICAL EVALUATION FOR DIFFERENT MECHANIZATION SYSTEMS IN POTATO PRODUCTION - Arkan M. A. Sedeeq (Mesopotamia Journal of Agriculture)
This research was carried out at three different regions in Ninevah governorate to study exploitation of agricultural technology criteria in potato production process during 2008. The study included three different mechanization systems in planted areas, Running Cost, Human Effort, Fuel Consumption, Capital Activity, Relative Cost & Machinery Degree. The results showed that the least values of ten production operations registered in the first system for properties of Running Cost (853.27) Dollar/hectare & Fuel Consumption (118.5) L/hr, while the first system showed the highest value in Capital Activity (2.1) & Machinery Degree (73.63%). The highest planted area (the third system) registered the least values in Human Effort (60.84) man.hr/hectare & Relative Cost (38.38%) properties.